Challenges and needs for social behavioural research and community engagement activities during the COVID-19 pandemic in rural Mozambique. Issue 1 (2nd January 2021) - Magaço, Amílcar; Munguambe, Khátia; Nhacolo, Ariel; Ambrósio, Contardo; Nhacolo, Felizarda; Cossa, Saquina; Macete, Eusébio; Mandomando, Inácio
ABSTRACT: After the Ebola outbreaks the world is again facing a challenge in which human behaviours and contact history play crucial roles in determining the trends in disease spreading within and across communities. With the onset of the recent coronavirus disease (COVID-19) pandemic, several issues related to conducting social behavioural sciences research and related community engagement activities arise, especially in rural areas of low-income countries, where the coverage of information and communication technologies (ICTs) is limited and their application on field-based research would imply a biased selection of relatively more privileged minorities with access to on-line and other communication platforms not requiring physical contact. This article enumerates and discusses the different technical challenges that social behavioural sciences research and community engagement activities face in times of public health emergencies caused by pandemics such as COVID-19. It also highlights the possibility of using alternative approaches to maintain the engagement with members of rural communities in research and social action activities, as well as the ethical challenges arising from such approaches.